Has the hippocampus really forgotten about space?. (December 2021) - Fiedler, Judit; De Leonibus, Elvira; Treves, Alessandro
Abstract: Several lines of evidence, including the discovery of place cells, have contributed to the notion that the hippocampus serves primarily to navigate the environment, as a repository of spatial memories, like a drawer full of charts; and that in some species it has exapted on this original one an episodic memory function. We argue that recent evidence questions the primacy of space, and points at memory load, whether spatial or not, as the challenge that mammalian hippocampal circuitry has evolved to meet. Highlights: Spatial correlates have been identified for neural activity in several places in the brain. Hippocampal activity can be seen to be selective for many other variables, besides spatial ones. Hippocampal involvement is typically needed when the memory load is massive. The mammalian dentate gyrus appears to be specialized to set up new memories when there are many already.